Fertilizantes como fuente de contaminación por Cd en suelos cultivados y arroz en la provincia de Guayas- Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2024)
Cadmium (Cd) is a toxic heavy metal that contaminates rice, and fertilizers represent a significantsource of this contamination. This study focused on detecting the presence of Cd in fertilizers,soils, and Oryza sativa plants in the cantons of Daule and Nobol in the province of Guayas, Ecuador.Nine samples of inorganic fertilizers were analyzed, and triplicate samples of soils and plantswere collected at 12 stations. Using an atomic absorption spectrophotometer, the maximumconcentration of Cd in the fertilizers was determined to be 41.30 ± 1.65 mg/kg, over 41 times therecommended limit. In the soil, the maximum concentration was 2.59 ± 0.31 mg/kg while, in theroots, leaves, and grains, the maximum concentrations were 0.50 ± 0.07, 0.44 ± 0.08, and 0.19 ±0.050 mg/kg, respectively. The results indicate that, in Nobol, the concentration of Cd in the soilwas over five times the limit allowed by Ecuadorian regulations, although the levels in the riceremained within the limits set by the European Union. This study indicates that fertilizers are asource of Cd contamination in these areas, with Nobol being the most affected canton.